Using Online Tools to Develop Higher Order Learning Among Tertiary Students - Page, Angela (Online Learning, 2022)
It is widely recognised that the development of higher order thinking skills is a fundamental goal of higher education. There are a variety of online tools that assist the development of student higher order thinking. In this paper, a process of scaffolding for the writing of higher-order questions enabled through peer learning activities is explored. Data collected over two years across five cohorts shows that there was an overall statistically significant improvement in the number of higher-order questions produced by students at the end of each unit. The findings reveal a viable peer teaching tool that can easily be embedded into existing programmes to develop the necessary critical thinking skills for higher education students.